Climate activism and its effects. (18th October 2020) - Fisher, Dana R.; Nasrin, Sohana
Abstract: As activism including climate strikes have become a common occurrence around the world, it is important to consider the growth in climate change‐focused activism and participation in social movements as a specific type of civic engagement. Although studies have analyzed climate activism and the climate movement, there is limited research that integrates it into the broader literature on civic engagement and which considers how these forms of engagement are related to specific climate outcomes. Here, we take a first step in understanding the material outcomes of these efforts. Specifically, we provide an overview of climate‐related activism as a form of civic engagement, paying particular attention to the targets of this activism and its environmental outcomes in terms of greenhouse gas emissions reductions. Then, we focus on one of the most common tactics to gain momentum in recent years: the school strike, which has mobilized a growing number of participants around the world. We discuss how the Coronavirus pandemic has changed the climate movement with much activism moving online. We conclude by discussing the overall state of the knowledge about the outcomes of climate activism, as well as highlighting the need for careful research to measure its effects across scale. This article is categorized under Policy and Governance > Private Governance of Climate Change The Social Status of Climate Change Knowledge > Climate Science and Social Movements Abstract : International Growth in Climate Strikes by Countries Participating and Individual Participants (Source: Fridays for Future, https://fridaysforfuture.org/statistics/list-countries ).